Unethical not to Investigate Radiotherapy for COVID-19 - Jerry M. Cuttler; Joseph J. Bevelacqua; S. M. J. Mortazavi (SAGE Publishing, 2020)
The primum non nocere letter by Boon et al. urged caution and careful examination of the evidence and logistics of low-dose radiotherapy in COVID-19 patients. This is exactly what was requested in March and what has occurred since late April 2020 when the first phase I/II clinical trial was approved at the Winship Cancer Institute, Emory University Hospital. The preprint of day-7 interim results by the investigators concluded, "In a small pilot trial of 5 oxygen-dependent patients with COVID-19 pneumonia, low-dose whole-lung radiation led to rapid improvement in clinical status, encephalopathy, and radiographic infiltrates without acute toxicity or worsening the cytokine storm. Low-dose whole-lung radiation appears to be safe, shows early promise of efficacy, and warrants larger prospective trials." Preliminary results from another clinical trial gave similar results. In conclusion, the authors believe it would be unethical not to investigate radiotherapy as a potential remedy against COVID-19 induced pneumonia